Reading Strategies in Spanish (L1) and English (L2) - Esther Zulay Rosas-Lobo (Revista Electrónica Educare)
The purpose of this study was to identify, detect and compare the reading strategies used in L1 and L2 by four Spanish-speaking university students, in order to find out in what stage of the reading process (before, during or after) they focused their strategic efforts. This research is based on the proposals by Solé (2000) and Díaz Barriga and Hernández (2000); contributions by Oxford (1990) and Barnett (1989) were significant in the interpretation of results. It is a qualitative field-study with semi-structured interviews, observation of participants and two reading comprehension tests for data collection; the information obtained was triangulated. One of the most remarkable findings is the general use of strategies before the L2 reading; although almost the same strategies were used in both texts, except for a group of strategies only used for L2. After comparing the results, it was found that the participants focused their strategic efforts in different stages of the reading process.